El balance de la independencia latinoamericana - Anderle, Ádám (Acta Hispanica, 2011)
This study is a historiographical overview of the literature of the Latin American wars ofindependence. It analyses the gains and losses, and poses the question: „has the world advanced" in the200 years of independence? The first part of the article concentrates on the events of the wars ofindependence and the developments in the 19th century focusing on the works of Francisco MoralesPadrón, Luis Navarro Garcia, Jose' Carlos Maridtegui, and the approach of the German historianManfred Kossok. In the secondpart the author presents the question of subdesarrollo and dependencia. Hediscusses the different interpretations for insufficient progress from the positivist viewpoints to the assessmentof the economists of the CEPAL. The novelty of this part is that it presents the results of the comparativeanalyses (Wittman, Pack, Zimdnyi) published in Hungarian historiography in the 1960s-1970s thatrevealed the similarities between the progress in Central-Eastern Europe and Latin America.